PERILAKU AKSESIBILITAS MASYARAKAT DAN EVALUASI YURIDIS KEABSAHAN KONTRAK PINJAMAN ONLINE ILEGAL - Hupita Damayanti; Adithya Nugraha; Vanza Parci Lukmana; Agus Septima Ridwan (INTELIGENSIA MEDIA, 2026)
This research aims to examine the phenomenon of illegal online loans through an interdisciplinary approach combining behavioral consumer psychology analysis and civil law evaluation. The issues raised concern the high accessibility of society to illegal online lending platforms and the validity of the standard digital contracts produced by such transactions. The method employed is normative legal research with an interdisciplinary approach integrating economic psychology and civil law dogmatics. The results reveal two main findings. First, society is driven to borrow from illegal platforms due to the impulse for instant gratification, manipulation of application visual architecture through dark patterns, socio-economic pressures encompassing emergency needs and the Fear of Missing Out phenomenon, and low financial and digital literacy. Second, the standard contracts of illegal online loans are declared invalid and null and void by operation of law for failing to fulfill the capacity requirement and lawful cause as stipulated in Article 1320 of the Indonesian Civil Code.